Exploring Early Childhood Education Teacher’s Beliefs About Steam Learning in Indonesia - Drupadi, Rizky; Zain, Azizah (Southeast Asia Early Childhood Journal, 2025)
In Indonesia, attention is being directed toward developing early childhood education (ECE), especially with innovative learning approaches such as STEAM (Science, Technology, Engineering, Arts, and Mathematics). The integrated STEAM concept can enrich children’s experiences and help children overcome everyday problems. This study explores early childhood education teachers’ perceptions of efforts to promote STEAM learning in the classroom and explores the challenges teachers experience in the application of STEAM learning. This study is descriptive research by using purposive sampling. Quantitative research methods were used for data collection, analysis, and interpretation, involving 117 early childhood education teachers. The results show that teachers feel comfortable talking about STEAM learning methods. On the other hand, teachers do not have sufficient knowledge to teach STEAM and critical thinking in early childhood. Furthermore, teachers do not understand enough about measurement in STEAM learning. It is reflected in several items that show that teachers need a lot of time to prepare for STEAM learning, do not have enough time in a day to teach STEAM, and do not have enough materials to do STEAM learning, inadequate availability of resources, and lack of early childhood education teacher training in STEAM. These findings support the need for teacher professional development practices to improve teachers’ understanding of the importance of STEAM and the practice of teaching STEAM to young children.